Volcano-tectonic dynamics of Deception Island (Antarctica): 27 years of GPS observations (1991–2018) - Rosado, B. (2020)
Deception Island (South Shetland Islands) is one of the most active volcanoes in Antarctica. In the 1988–1989 austral summer, after the most recent eruptive process on the island (1967–1970), monitoring of volcanic activity through geophysical and geodetic techniques was resumed by Spanish and Argentinean scientists. In order to monitor the island's tectonic and volcanic behavior, a geodetic network was deployed. Currently, this network consists of 15 geodetic benchmarks located around Port Foster, Deception's inner bay open to the sea. Two additional geodetic benchmarks were installed outside Deception Island to be used as reference benchmarks for the differential positioning strategy. Since 1991–1992, geodetic ground-displacement velocities between the successive austral summer Antarctic campaigns have been computed and analyzed. The overall geodynamic behavior of Deception Island within the South Shetland Islands, Antarctic Peninsula and Bransfield Basin regional environment has been analyzed from geodetic ground-displacements. Results obtained demonstrate that Deception and Livingston island have a similar behavior derived from the Bransfield Basin extension and the Phoenix micro-plate subsidence processes. However, Deception Island is also highly influenced by its volcanic activity. Deception Island's volcanic behavior between 1991 and 2018 is shown by the velocity field, strain tensors and pressure source evolution obtained from the ground-displacements at the geodetic benchmarks. During this time period, it is possible to identify different inflation and deflation phases separated by transitional (or mixed) stages of extension without uplift and compression without subsidence. The most representative inflation and deflation periods were analyzed in detail, to show how they correlate with high and low seismic activity, respectively. The transitional or mixed stages, seem to be the precursors of the next inflation or deflation phase being the Bransfield basin rifting and NW-SE extension the potential related process. Finally, we have analyzed the processes that occurred prior to the volcanic unrests of 1999–2000 and 2012–2013. In both cases, an increase in detected seismic activity and/or soil and seawater temperature was observed and a mixed phase of extension without uplift seems to be precursory to the volcanic unrest. The correlation between the inflation processes, identified by ground-displacement of the network geodetic benchmarks, the increase in seismicity and the increment of soil and seawater temperature makes these transitional mixed phases potential precursors of Deception Island's volcanic unrest periods.